Niche differentiation and colonization of a novel environment by an asexual parasitic wasp. (20th March 2013) - Forbes, A. A.; Rice, L. A.; Stewart, N. B.; Yee, W. L.; Neiman, M.
Abstract How do asexual taxa become adapted to a diversity of environments, and how do they persist despite changing environmental conditions? These questions are linked by their mutual focus on the relationship between genetic variation, which is often limited in asexuals, and the ability to respond to environmental variation. Asexual taxa originating from a single ancestor present a unique opportunity to assess rates of phenotypic and genetic change when access to new genetic variation is limited to mutation. Diachasma muliebre is an asexual Hymenopteran wasp that is geographically and genetically isolated from all sexual relatives. D. muliebre attack larvae of the western cherry fruit fly (Rhagoletis indifferens), which in turn feed inside bitter cherry fruit (Prunus emarginata) in August and September. R. indifferens has recently colonized a new host plant with an earlier fruiting phenology (June/July), domesticated sweet cherries (P. avium), and D. muliebre has followed its host into this temporally earlier niche. We tested three hypotheses: 1) that all D. muliebre lineages originate from a single asexual ancestor; 2) that different D. muliebre lineages (as defined by unique mtDNA haplotypes) have differentiated on their ancestral host in an important life‐history trait, eclosion timing; and 3) that early‐eclosing lineages have preferentially colonized the new sweet cherry niche. We find that mitochondrial COI and microsatellite data provide strong support for a single ancestral origin for all lineages. Furthermore, COI sequencing revealed five mitochondrial haplotypes among D. muliebre, and individual wasps possessing one distinctive mitochondrial haplotype (haplotype II) eclosed as reproductive adults significantly earlier than wasps with all other haplotypes. In addition, this early‐eclosing lineage of D. muliebre is one of two lineages that have colonized the P. avium habitat, consistent with the preferential colonization hypothesis. These data suggest that D. muliebre has evolved adaptive phenotypic variation despite limited genetic variation, and that this variation has subsequently allowed an expansion of some wasps into a novel habitat. The D. muliebre system may allow for in‐depth study of adaptation and long‐term persistence of asexual taxa.